2013
DOI: 10.1590/s0103-21002013000300005
|View full text |Cite
|
Sign up to set email alerts
|

Fatores associados à adesão ao tratamento de pacientes com diabetes mellitus

Abstract: Objective: Investigating the association between adherence to treatment of type 2 diabetes mellitus and sociodemographic, clinical and metabolic control variables. Methods: Cross-sectional study with 423 patients with diabetes mellitus. The Fisher's exact test and logistic regression models were used to investigate the association between adherence to treatment and the studied variables.Results: There was no association between adherence to treatment of T2DM and socio-demographic and clinical variables. It was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
31
2
56

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(93 citation statements)
references
References 15 publications
4
31
2
56
Order By: Relevance
“…T2DM patients who are currently smoking are 6.9%. Comparing to a study done in Germany reported that prevalence of smoking in T2DM was 17.3% patients [37,40]. In this study the results found 6.9% was lower.…”
Section: Discussioncontrasting
confidence: 51%
“…T2DM patients who are currently smoking are 6.9%. Comparing to a study done in Germany reported that prevalence of smoking in T2DM was 17.3% patients [37,40]. In this study the results found 6.9% was lower.…”
Section: Discussioncontrasting
confidence: 51%
“…The Cronbach alpha is considered a good measure of internal consistency; values must range from 0.70 to 0.95. (17) The value found in our study was 0.81, which suggested that Brazilian version of the Acceptance of the Disease Scale is reliable.…”
Section: Discussionsupporting
confidence: 55%
“…Probably, for having less time of adaptation with the disease and its treatment, the individuals with less time of diagnosis suffer with more immediate repercussions, such as difficulty in accepting the treatment with applications of insulin, self glycemic monitoring, alimentary restriction, possible episodes of hypoglycemia, among other conditions related to the illness and its treatment. According to Faria et al 23 , the longer time of diagnosis of DM type 2 result in higher knowledge on the disease, as well as better understanding and handling of the therapeutic scheme. Educative interventions destined to facilitate the development of specific skills to face diabetes may improve the quality of life of patients carrying this disease 24 .…”
Section: Discussionmentioning
confidence: 99%